Effectiveness of African herbal preparations against multidrug-resistant Klebsiella pneumoniae: A systematic review - Rachel A․ A․ Akorful; Karikari Asafo-Adjei; Fleischer C․ N․ Kotey; Eric S․ Donkor (Scientific African)
Multidrug-resistant Klebsiella pneumoniae (MDR-Kp) poses a significant public health challenge due to limited treatment options and growing antimicrobial resistance (AMR). The rise in MDR-Kp infections underscores the critical need for new strategies against antibiotic resistance, especially in Africa, where AMR is a pressing concern. This systematic review evaluated the antimicrobial activity of herbal preparations against MDR-Kp by assessing parameters such as minimum bactericidal concentration (MBC), zone of inhibition, and minimum inhibitory concentration (MIC). A literature search was done following the PRISMA guidelines, and relevant articles from PubMed, Scopus, and ScienceDirect were included. The search identified 2094 articles, of which 848 were selected for a full assessment and 31 were included. Data extraction included information on plant scientific names, botanical families, plant parts, country of origin, extract types, isolated compounds, and antimicrobial parameters. Of the 124 plants studied, Withania frutescens L., Plumbago zeylanica, Plectranthus glandulosus, Eruca sativa, and Donella welwitschii, emerged as plants that could be further explored for anti-MDR-Kp therapeutics. Further research is needed to explore their mechanisms of action, active compounds, and potential synergies. Integrating traditional knowledge with modern healthcare practices, standardised research methodologies, and clinical validations can advance plant-based therapies. Additionally, conservation efforts are vital to preserve the biodiversity of these medicinal plants, ensuring their availability for future research and therapeutic use, while supporting environmental and public health.